Imaging of the adult male urethra, penile prostheses and artificial urinary sphincters - Subramaniyan Ramanathan (14158842) (2019)
To discuss the imaging appearances of various pathologies affecting adult male urethra and to review the role of imaging in the assessment of artificial urinary sphincters and penile prostheses. Diagnosis of common male urethral diseases heavily depends on two conventional fluoroscopic techniques namely retrograde urethrography and voiding cystourethrography. These are useful in evaluating common urethral diseases like traumatic injury, infections, and strictures. Cross-sectional imaging can be useful in evaluating periurethral pathologies. Artificial urinary sphincters, slings, and periurethral bulking agents are used in the management of urinary incontinence and imaging can be utilized to detect complications in these devices. Cross-sectional imaging especially MRI plays a significant role in evaluating the different types of penile prostheses and their malfunctioning. Other Information Published in: Abdominal Radiology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s00261-019-02356-x